Neutrophil-Lymphocyte Ratio as a Screening Test for Preeclampsia in the First and Early-Third Trimesters of Pregnancy: A Cohort Study: - Zare, Marjan; Faraji , Azam; Nourani, Zahra; Askary, Elham; Kasraeian , Maryam (Galen Medical Journal, 2022)
Background: Preeclampsia (PEC), affecting 5-10% of all pregnancies, is a multisystem disease diagnosed by hypertension (HTN) and protein in the urine or multi-organ problems without signs of proteinuria occurring after 20 weeks of gestation. PEC is the most common cause of maternal death and can lead to premature delivery. The current study aimed to investigate the accuracy of neutrophil-lymphocyte ratio (NLR) for predicting PEC in the first and early-third trimesters of pregnancy in a normal population in the south of Iran. Materials and Methods: A large-scale cohort study was performed from early pregnancy onward during November 2018-2019 in a normal population from Fars province, Southwest Iran. Four hundred forty-nine pregnant women were followed prospectively, and normal blood pressure (normotensive), gestational HTN, and PEC groups were compared in terms of white blood cells (WBC) count, neutrophil, lymphocyte, and NLR. Results: The serum levels of WBC count, neutrophil, and NLR significantly increased from the first to the early-third trimesters of pregnancy (P<0.05); however, lymphocytes decreased (P<0.05). The NLR cut-off points for predicting PEC were 2.79 (sensitivity=86.7% and specificity=92.6%) in the first and 3.2 (sensitivity=90.5% and specificity=79.4%) in the early-third trimesters. Conclusion: Our findings revealed that NLR could be an accurate predictive factor for PEC in the first and early-third trimesters of pregnancies; however, more studies are needed to investigate the immunomodulatory drugs for the prevention of PEC.